Braided Words: Re-storying Holocaust Testimony through Indigenous-Jewish Dialogue - chalmers, jason; Collier-Jarvis, Krista (Canadian Jewish Studies / Études juives canadiennes)

(untitled) (Association for Canadian Jewish Studies / Association d’études juives canadiennes, 2025)
This article explores how material culture and shared testimony can be the basis for relationship-building between Indigenous peoples and Jews in Canada. It relies on Indigenous Métissage, a decolonizing methodology that uses artefacts to re-story Indigenous-settler relations. Drawing on their experiences as intergenerational survivors of the Holocaust and of Residential Schools, the authors apply this practice to the wartime diary of Melania Weissenberg, a Polish Jew who survived the Holocaust and immigrated to Canada as a war orphan in 1948. By exploring key points of entanglement, the authors create a braid wherein Mi’kmaw and Jewish narratives overlap, intersect, and knot together. This sort of dialogue can illuminate the structures and processes of settler colonialism while beginning to transform Indigenous-settler relations. Although the analysis addresses histories and legacies of genocide, it also shows how Indigenous and settler experiences are related through tradition, place, and memory.